Vaccine Can Induce CD4-Mediated Responses to Homocitrullinated Peptides via Multiple HLA-Types and Confer Anti-Tumor Immunity - Cook, Katherine; Xue, Wei; Atabani, Suha; Symonds, Peter; Al Omari, Abdullah; Daniels, Ian; Shah, Sabaria; Choudhury, Ruhul Hasan; Weston, Daisy; Metheringham, Rachael; Brentville, Victoria; Durrant, Lindy (Frontiers in Immunology, 2022)
Homocitrullination is the post translation modification (PTM) of the amino acid lysine to homocitrulline also referred to as carbamylation. This PTM has mainly been studied in relation to autoimmune diseases including rheumatoid arthritis. Homocitrullination of lysines alters their charge which can lead to generation of neoepitopes that are differentially presented by MHC-II and induce modification-specific immune responses. Homocitrullination is often considered a process which triggers autoimmune disease by bypassing self-tolerance however, we suggest that homocitrullination may also have an alternative role in immune responses including protection against cancer. Here we demonstrate that immune responses to homocitrullinated peptides from three different proteins can be induced via multiple HLA-types. Immunization of Balb/c or HLA-transgenic DR4 and DR1 mice can induce modification-specific CD4 mediated IFNγ responses. Healthy human donors show a clear repertoire for the homocitrullinated Vimentin peptide (Vim116-135Hcit), with modification-specific and oligoclonal responses. Importantly, in vivo homocitrulline specific Vim116-135Hcit, Cyk8 371-388Hcit and Aldo 140-157Hcit responses are able to confer an anti-tumor effect in the murine B16 melanoma model. The Vim116-135Hcit anti-tumor response was dependent upon tumor expression of MHC-II suggesting the direct recognition of PTMs on tumor is an important anti-tumor mechanism. Cancer patients also have a CD4 repertoire for Vim116-135Hcit. Together these results suggest that homocitrulline-specific immune responses can be generated in healthy mice and detected in human donors through a variety of HLA-restrictions. Immunization can induce responses to Vim116-135Hcit, Aldolase 140-157Hcit and Cyk8 371-388Hcit which provide anti-tumor therapy across several HLA-types. Our results advance our understanding of homocitrulline-specific immune responses, with implications for a number of fields beyond autoimmunity, including tumor immune surveillance.